The Influence of Age, Body Mass Index, Gestational Weight Gain, Parity, Oxytocin Dosage, Receiving Pain Medications, and Anxiety on The Duration of Labor in Parturient Women at Term - Chaiyo, Sasipriya; Limruangrong , Piyanun; Phahuwatanakorn , Wanna (Journal of The Royal Thai Army Nurses, 2024)
This study examined the influence of age, body mass index, gestational weight gain, parity, oxytocin dosage, receiving pain medications, and anxiety over duration of labor in parturient women at term. The sample was 127 parturient women with natural birth. Data were collected by using a demographic data questionnaire and an anxiety during labor questionnaire. Data were analyzed with descriptive statistics and multiple regression analysis. According to the findings, the sample had a mean duration of labor of 557.04 minutes in Stage 1 of labor and 19.26 minutes in Stage 2 of labor, a mean of 575.81 minutes in both stages of labor. The factors with influence over duration of labor among parturient women with statistical significance consisted of parity (ß = -.22, p = .013), oxytocin dosage (ß = -.24, p = .005), and anxiety (ß = .37, p < .001). The factors were able to explain duration of labor among parturient women at 25.30 percent (R2 = .253, F = 5.765, p< .001).